PLGA/TPGS nanoparticles for docetaxel delivery: The pegylation effect on nanoparticle physicochemical properties and uptake and cytotoxicity in prostate cancer cells - Silva, Lívia de Queiróz Carvalho (2025)
Prostate cancer is the most common malignancy in men worldwide and docetaxel (DTX) is the treatment of choice. However, both the drug and formulation excipients for drug solubilization can cause side effects. In this context, the development of polymeric nanoparticles offers advantages to improve drug delivery and reduce toxicity. In the present work, factorial design was used to evaluate the effect of the amount of poly(L-lactide-co-glycolide) (PLGA) or poly(L-lactide-co-glycolide acid-polyethylene glycol) (PLGA-PEG), D-Alpha-Tocopheryl Polyethylene Glycol Succinate (TPGS) and ratio between aqueous and oily phases on the nanoparticle characteristics. The nanocarriers were characterized regarding particle size, polydispersity, zeta potential, DTX encapsulation efficiency, morphology by transmission electron microscopy, DSC, TGA and FTIR. It was evaluated in vitro for cytotoxicity and cellular uptake in prostate cancer cells. Pegylated nanoparticles, which have a different composition (TPGS%, AP:OP ratio), reduced the nanoparticle size to 105.97 ± 5.16 nm, in PDI 0.13 ± 0.03, zeta potential of -34.73 ± 1.19 mV and increased the encapsulation efficiency to 96.78 ± 1.20%. Characterization by DSC, TGA and FTIR confirmed drug encapsulation and showed colloidal stability. Pegylated nanoparticles were more stable upon serum incubation and adsorbed less proteins. In conclusion, the pegylation of the nanoparticles affected the physicochemical parameters. Also, the pegylation of nanoparticles decreased uptake by macrophages. Finally, cellular uptake and cell cytotoxicity were higher in tumor cells when compared to non-tumor cells, although they were not affected by pegylation.